Analisis Geoteknik Ditinjau dari Karakteristik Kuat Geser Material Longsoran - Edoward Janto Parulian Pardede (Syntax Idea)
This research aims to analyze geotechnical aspects in the context of slope stability and soil landslides. The main focus of this research is on the shear strength characteristics of materials, which are a key factor in predicting the potential for landslides. The methods used in this research involve field geotechnical data collection, laboratory testing to determine geotechnical parameters, and numerical modeling to analyze slope stability. The research results indicate that the shear strength of landslide materials is a crucial factor in evaluating slope stability. Variations in geotechnical properties of materials, such as water content, soil texture, and density, have a significant impact on shear strength and the potential for landslides. Additionally, numerical analysis shows that environmental factors, such as rainfall and human activities, can also influence slope stability. This research provides a better understanding of the relationship between shear strength characteristics of materials and slope stability, serving as a basis for the development of landslide risk mitigation strategies. This has important implications for disaster management and safe land use planning in landslide-prone areas.